Development of tomato inspection and grading system using image processing - Hashim, Nik Mohd Zarifie; Mohamad, Nor Hafiza; Zakaria, Zahriladha; Bakri, Hairul (International Journal Of Engineering And Computer Science, 2013)
Nowadays the food quality is became a major issue in health care. It is difficult to find the best food quality by ourselves in the market. This system was created to specify the quality of specific product. Quality is commonly related with product and it is very important to satisfy the customer’s desire. The system is focus on the quality of food which has impact on our health. For this proposed system, a tomato is been used as the product that to be tested for food quality. This paper explained a technique for automatically detecting tomatoes skin surfaces in digital color images. The system describes two-step process which the first is detecting regions which are likely to contain tomatoes skin in the color images and then extracts information from these regions which might indicate the location of a tomato in the image. An inspection and grading system for tomato that has been loaded as an image and after that the image passed through the brightness process. After the image taken from webcam and already loaded onto the system then the system will process the both images (captured and input) by reading the color in each of pixel images. The processes of the images in this system needed to display the percentages value of color in order to classify the grade of tomato. Matlab software and its image processing toolbox have been used in images processing and analysis. As the result, Graphic User Interface (GUI) for tomatoes inspection and grading system by using Matlab software version 7.0.4 are achieved. For the future recommendation this system can be upgraded by adding the various types of fruits or vegetarians.